DEMOCRATIC TRANSIT MODEL IN ITS THEORETICAL AND EMPIRICAL DIMENSIONS - Гайданка, Є.І. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
On the basis of theoretical and methodological background there has been elaborated a model of the democratic transit investigation. Classic transitology points out 3 institutional stages within the democratic transit. They usually occur in close succession, the stages being as follows: liberalization, democratization, democracy consolidation. Empirical indexing has been a reliable methodological tool making it possible to either confirm or deny actual efficiency of theoretical constructions. Among the major applied democracy measuring techniques one should name Freedom House and Bertelsmann Found.